Molecular characterization of new candidate genes for familial thyroid cancer - Gomes, Inês Fernandes (2016)
GOMES, Inês Fernandes - Molecular characterization of new candidate genes for familial thyroid cancer. Coimbra : [s.n.], 2016. Dissertação de Mestrado.